The Impact of Self-Paced Online Training on Self-Efficacy and Work Engagement In Private Universities, Bali, Indonesia - Ni Made Dwi Puspitawati; Andika, Ary Wira; Paramita, Ida Ayu Putu Utami (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The Covid-19 pandemic has brought changes in the socio-cultural, economic and educational fields. This event is an important concern in maintaining the performance and condition of lecturers when all activities carried out must use online media. Work enthusiasm is the key to maintaining the desire to work without coercion. This can be achieved if lecturers remain engaged through self-paced online training and self-efficacy. The specific objective of this study is to determine the effect of self-paced online training on self-efficacy and work engagement in Private Universities, Bali, Indonesia. The population is all lecturers at private universities in Bali. The sample in this study were 100 people. The sampling technique used snowball sampling. Data collected through questionnaires followed by validity and reliability tests. Data were analysed using SEM-PLS. The results showed that (1) self-paced online training had a positive and significant effect on work engagement, (2) self-paced online training had a positive and significant effect on self-efficacy, (3) self-efficacy had a positive and significant effect on work engagement. This has the implication that through online training activities can increase confidence in the abilities possessed by lecturers so as to make them more attached to their work. Keywords: private universities, self-efficacy, online training, work engagement